Du lexique aux talismans : occurrences de la peste dans la Corne de l’Afrique du XIIIe au XVe siècle - Marie-Laure Derat (Afriques)
Recent researches on plague invite scholars to enlarge the chronology and the geography of the Black Death. If, according to the commonly admitted chronology, the Black Death occurred in Western Europe from 1347 to 1350, it is now evident that outbreaks of the Black Death occurred in the Near and Middle East long after the mid-14th century. In Egypt, historical sources show outbreaks of the plague during the 15th century, with regular waves in 1403, 1407, 1430, 1460, and later. Many Ethiopian written sources refer to pandemics shaking the kingdom and causing thousands of deaths. Chronicles and lives of Saints abound in scattered notations on the need to bury the victims of these pandemics with a particular process. The Saints embody figures of miraculous healing, and the reading during Mass services of hagiographic texts dedicated to these Saints provided hope to the victims of the pandemics. On the basis of these testimonies, however, it is often impossible to identify what disease was the cause of the pandemic. The synchrony between pandemics observed in Egypt and those observed in Ethiopia, as well as the diplomatic, commercial, and religious links between Ethiopia and Egypt, permit us to interpret some of the pandemics described in the Ethiopian sources as plague pandemics. After a presentation of Ethiopian sources dealing with pandemics from the 13th to the 15th century, the questions of the vocabulary used to designate epidemics, and the identification of the diseases involved, the paper then provides an overview of plague outbreaks in regions neighbouring Ethiopia, particularly in Egypt and the Arabian Peninsula, combined with an examination of the Horn of Africa’s connections with these regions. The last section focuses on social responses to epidemics in Ethiopia in an attempt to identify and singularize them, according to the attitudes adopted. The introduction of the commemoration of Saint Roch in the Ethiopian synaxary and in the collections of Ethiopian magical prayers is finally resolving the doubt about the likelihood of a plague epidemic in Ethiopia.